Learning number game with interactive projection for students of Sepuluh Nopember Surabaya Kindergarten - Sudaryanto, Aris; Basuki, Achmad; Nurindiyani, Artiarini Kusuma; Muhammad, Farhan; Sa’dyah, Halimatus; Akbar, Zulhaydar Fairozal; Revindasari, Fony; Suhardiman, Marvel Natanael; Lazuardy, Ryan Ramadhan; Ash Shidiq, Ahmad Fauzan (Institut Teknologi Dirgantara Adisutjipto, 2023)
Based on a survey by the Association of Indonesian Internet Service Providers (APJII) in 2017, 143.26 million Indonesians used the internet. This condition is exacerbated by the “online learning” during the pandemic which forces children to be exposed to gadgets more than they should, which is more than 2 hours a day. Even though gadgets can affect children's behavior. It is proven that 66 out of 100 children have a high level of gadget addiction. The negative impact of gadgets on children is caused by the one-way communication between children and gadgets. This means that the instructions only come from the gadget while the child absorbs them without any significant response. Based on these problems, we makes a two-way interactive game that can be an alternative game for children. Game Numberpedia is played with a projector, then children can play interactively by touching the image. The Numberpedia game was then donated and played at Sepuluh Nopember Surabaya kindergarten as part of community service activities. The response from the children after playing the Numberpedia game shows that this game has clear and interesting audio visuals, and arouses the enthusiasm of children to play it.